2013
DOI: 10.3989/scimar.03632.28b
|View full text |Cite
|
Sign up to set email alerts
|

Age, growth and mortality of <i>Pontinus kuhlii</i> (Bowdich, 1825) (Scorpaeniformes: Scorpaenidae) in the Gorringe, Ampère, Unicorn and Lion seamounts

Abstract: SUMMARY: Age and growth of Pontinus kuhlii were studied using otoliths of 153 males and 148 females, with males having a greater length (and age) than females. A high level of agreement was achieved among readers. Due to gear selectivity, only ages above 7 years (males) and 8 years (females) were estimated in whole otoliths. To estimate length-at-age in younger specimens, backcalculation was also considered but its use in otoliths with ages greater than 22 years was not possible because the growth rings were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…Plasticity in sexual dimorphism is a possible explanation for the location‐specific differences we observed in rosefish, as studies have reported the existence and lack of sex‐specific differences in growth of this species (Kelly 1999, Massutı́ et al 2000, Sequeira et al 2009). In rockfish, females grew slightly faster than males but the largest and oldest individuals were all male which is in line with the sexual dimorphism pattern commonly observed in rockfish (López Abellán et al 2007, Barros Paiva et al 2013).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Plasticity in sexual dimorphism is a possible explanation for the location‐specific differences we observed in rosefish, as studies have reported the existence and lack of sex‐specific differences in growth of this species (Kelly 1999, Massutı́ et al 2000, Sequeira et al 2009). In rockfish, females grew slightly faster than males but the largest and oldest individuals were all male which is in line with the sexual dimorphism pattern commonly observed in rockfish (López Abellán et al 2007, Barros Paiva et al 2013).…”
Section: Discussionsupporting
confidence: 86%
“…Both species are commercially valuable deep‐water scorpaenids, commonly found at depths of 200–1000 m and 100–450 m, respectively. The rosefish is widely distributed in the eastern Atlantic Ocean (Sequeira et al 2009) whereas the rockfish has a more southern distribution ranging from Portugal to Angola including the Macaronesian region (Barros Paiva et al 2013). Maximum age reported is 43 years for rosefish (Sequeira et al 2009) and 30 years for rockfish (Barros Paiva et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Results from this study indicate the bias of females towards smaller lengths and of males towards larger ones as already reported for other scorpaenid species such as Scorpaena maderensis Valenciennes, 1833 (see La Mesa et al 2005), Scorpaena loppei Cadenat, 1943 (see Ordines et al 2012), Pontinus kuhlii (Bowdich, 1825) (see Paiva et al 2013), Helicolenus dactylopterus (Delaroche, 1809) (see Massuti et al 2000), and also for Scorpaena notata of Balearic Islands (Ordines et al 2009). The reproductive strategy showed by several species within the scorpaenid family such as the development of a gelatinous matrix within the ovary (Muñoz 2010) imply that females have a higher energetic cost during reproduction than males and can justify the growth differences between sexes.…”
Section: Discussionsupporting
confidence: 50%
“…To estimate von Bertalanffy growth parameters, different approaches were needed for the two species. The scarcity of young individuals of T. lyra precluded the adjustment of the von Bertalanffy equation to the agelength key and justified the use of two additional approaches: the back-calculation method and a combined method (Paiva et al 2013, Gordo et al 2016. The combined methodology showed the best adjustment to the data and the most realistic growth parameters.…”
Section: Trigla Lyra Chelidonichthys Cuculusmentioning
confidence: 99%